2023
DOI: 10.3390/life13081650
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Related Knee Osteoarthritis—Current Concepts

Russka Shumnalieva,
Georgi Kotov,
Simeon Monov

Abstract: The knee is the joint most frequently involved in osteoarthritis and represents a significant contributor to patient morbidity and impaired functional status. Major risk factors include genetics, age, sex, mechanical load and obesity/metabolic syndrome. Recent studies highlighted the role of obesity and metabolic syndrome in the pathogenesis of knee osteoarthritis not simply through increased mechanical loading but the systemic effects of obesity-induced inflammation. The current concept of knee osteoarthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…KOA is a musculoskeletal disease characterized by progressive cartilage loss, usually presenting by chronic pain, limitation of movement, and disability (22). In the current work, the median WOMAC score was 48 with IQR: 39-63, so severe knee affection was remarkable among most of OA patients as the total WOMAC score (a disease-speci c grading scale) is 96.…”
Section: Discussionmentioning
confidence: 61%
“…KOA is a musculoskeletal disease characterized by progressive cartilage loss, usually presenting by chronic pain, limitation of movement, and disability (22). In the current work, the median WOMAC score was 48 with IQR: 39-63, so severe knee affection was remarkable among most of OA patients as the total WOMAC score (a disease-speci c grading scale) is 96.…”
Section: Discussionmentioning
confidence: 61%
“…Conversely, KOA could have caused VF because of the strain on the spine. In addition, obesity has already been reported to be associated with KOA [39]. Therefore, asymptomatic VFs may not explain all causal relationships with obesity and KOA.…”
Section: Discussionmentioning
confidence: 97%
“…To investigate the direct causal effect of diet on KOA, we performed Multivariate Mendelian randomization (MVMR) analyses. In previous studies, it was found that KOA may be strongly influenced by obesity [ 29 ], hypertension [ 15 ], diabetes mellitus [ 30 ], and prolonged standing [ 31 ]. Therefore, we corrected for the potential interference of obesity, BMI, hypertension, diabetes and prolonged standing in the MVMR analysis.…”
Section: Methodsmentioning
confidence: 99%